Peran Pembelajaran Pendidikan Agama Kristen Sebagai Upaya Menghadapi Era Globalisasi untuk Penguatan Karakter Siswa di SMA Negeri 1 Sijamapolang - Usu Marlundu Simanullang (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
The era of globalization brings great challenges to the world of education, especially in shaping the character of the younger generation. Christian Religious Education (PAK) learning has a very important role in facing these challenges, especially in strengthening students' character. This study aims to analyze the role of PAK learning in building students' character amidst the flow of globalization. The method used in this study is a qualitative approach with descriptive analysis, through data collection from interviews, observations, and literature studies. The results of the study show that PAK learning not only teaches religious values, but also provides a solid moral foundation for students in facing the negative effects of globalization. PAK plays a role in shaping students' attitudes of discipline, responsibility, tolerance, and integrity, which are very important in facing the changing times. Therefore, Christian religious education is one of the important means in strengthening students' character so that they are able to adapt well in the challenging era of globalization.